2019
DOI: 10.3892/ol.2019.10761
|View full text |Cite
|
Sign up to set email alerts
|

Heavy‑ion beam irradiation inhibits invasion of tongue squamous cell carcinoma Tca8113 cells

Abstract: Tongue squamous cell carcinoma (TSCC) is a common malignant tumor type with aggressive biological characteristics, located in the oral and maxillofacial region. Vascular endothelial growth factor (VEGF) and matrix metalloproteinases (MMPs) have been implicated in the invasion and metastasis of various malignant tumor types, such as lung cancer and gastric carcinoma. High linear energy transfer (LET) particle irradiation has several advantages over conventional X-rays in suppressing the invasion and metastasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The commonly used single dose of conventional 2 Gy irradiation, resulted in an increase in VEGF secretion in B16F10 cells. In line with our findings, a decrease in VEGF expression was observed in Tca8113 cells after C-ion irradiation, while there was no significant change in the X-ray group ( 45 ). Furthermore, the expression of VEGF was found to be elevated in breast cells after X-ray irradiation ( 46, 47 ).…”
Section: Discussionsupporting
confidence: 91%
“…The commonly used single dose of conventional 2 Gy irradiation, resulted in an increase in VEGF secretion in B16F10 cells. In line with our findings, a decrease in VEGF expression was observed in Tca8113 cells after C-ion irradiation, while there was no significant change in the X-ray group ( 45 ). Furthermore, the expression of VEGF was found to be elevated in breast cells after X-ray irradiation ( 46, 47 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, the metastasis of lung cancer is a major cause of treatment failure ( 2 ). Carbon ions with high LET rays ( 12 C 6+ ) can inhibit the metastasis of tumor cells by their advantages in physics and biology ( 3 , 4 ). Radiation induces bystander effect (RIBE) refers to the plethora of biological phenomena occurring in non-irradiated cells as a result of signal transmission from an irradiated cell ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the degradation of some macromolecules and basement membranes in the extracellular matrix can promote the metastasis and invasion of various cancers. Overexpression of MMP2 and MMP9 is closely related to tumor invasion and metastasis 17 . The present study showed that carbon ions could inhibit GPX4 and MMP2, and promote E‐cadherin expression in tumor cells.…”
Section: Discussionmentioning
confidence: 50%